(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study to assess knowledge, attitudes and factors related to HPV vaccine among students of Hanoi Medical University. Participants and methods: A cross-sectional study was conducted with 313 students, collecting data about knowledge, attitudes, and behaviors regarding the HPV vaccine through questionnaires. Results: Female students had a higher awareness of HPV compared to males (55.9% vs. 23.3%). However, the vaccination rate for HPV was similar between male (31.6%) and female (31.7%) students. The main reasons for not getting vaccinated were high costs and concerns about side effects. Female students were more likely to receive the vaccine. Conclusion: Health education should be strengthened to raise awareness about the HPV vaccine and encourage vaccination, particularly among male students.